Obesity, Inflammation and Cancer - Dannenberg, Andrew J.; Berger, Nathan A.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2013)
In addition to their metabolic and endocrinologic effects, obesity and adipose tissue have now been shown to be associated with chronic low grade inflammation resulting in cellular and humoral factors of which the latter may act by endocrine, paracrine and autocrine mechanisms. These inflammatory mediators have increasingly been suggested as contributing to the obesity link to carcinogenesis and cancer promotion. Obesity, Inflammation and Cancer focuses on recent developments and cutting edge research pointing to inflammation and inflammatory factors as key mediators of this linkage. It also describes possible strategies for targeting inflammation as an approach to cancer prevention and control. Students, researchers and clinicians, especially those interested in the relation of obesity to cancer and the role of inflammation and its impact on cancer, will find this volume particularly useful. It provides important insight on the role of inflammation in cancer etiology and progression and serve as a platform for developing future research in this area.
Preface -- Obesity, Inflammation and Insulin Resistance -- Inflammasomes and Obesity -- Uncoupling Obesity from Cancer: Bromodomain Co-regulators that Control Inflammatory Networks -- Adipose Tissue Macrophages in Obesity, Inflammation and Cancer -- Dietary Fats as Mediators of Obesity, Inflammation and Colon Cancer -- Inflammation, Obesity, Barrett$1 (Bs Esophagus and Esophageal Adenocarcinoma -- Obesity, Inflammation and Breast Cancer -- Obesity, Inflammation, Nonalcoholic Fatty Liver Disease and Hepatocellular Carcinoma -- Obesity, Inflammation and Prostate Cancer -- Pharmacologic Interventions With NSAIDs -- Omega-3 Fatty Acids in Cancer Prevention and Control: A Membrane Perspective -- Natural Products as Anti-inflammatory Agents -- Calorie Restriction and Cancer Prevention: Established and Emerging Mechanisms -- Vascular Targeting of Adipose Tissue -- Anti-Inflammatory Effects of Exercise -- Index.s
Keywords: Medicine; Oncology; Human physiology; Biomedicine; Cancer Research; Human Physiology; Biomedicine general